EFFECT OF CONSUMING PREBIOTIC BISCUIT BASED ON PROTEIN QUALITY EVALUATION BY IN VIVO METHOD - Zhafarinnadia, Moura; Sumanti, Debby Moody; Hanidah, In-In; Barqin, Gesa Aldin (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2024)
ABSTRACTBackground: Prebiotic biscuits are biscuits made from composite flour consisting of plaintain hump flour, yellow sweet potato flour, black soybean flour and black soybean sprouts flour. The combination of the resulting composite flour is known to have a higher nutritional value when compared to wheat flour. However, prebiotic biscuits contain certain ingredients such as protein or food fiber whose structure must be known in advance to modify their functional properties after consumption. Objective: The evaluation of protein quality was carried out to determine the effect of giving “BonnisA” prebiotic biscuits with different protein sources in increasing the quality of protein in Vivo. Methods: Research method used was experimental which was analyzed descriptively with 4 treatments 5 times. The object used in this experiment are male wistar rats (Sprague Dawley) weighing 150 - 220 g, and the treatments were given were black soybean flour prebiotic biscuits, prebiotic biscuits with black soybean sprouts flour, standard rations and egg white flour. Results: The results obtained showed that the highest increase in body weight of rats was treated with the prebiotic biscuit BonnisA black soybean flour of 13.29%. Furthermore, the evaluation of protein quality on rats was increased in black soybean flour prebiotic biscuits based on true digestibility (TD) (99.21%), biological values (BV) (99.25%), and net protein utilization (NPU) (98.47%).Conclusions: The evaluation of protein quality showed that there was a significant difference (p <0.05) between the provision of black soybean flour prebiotic biscuits and prebiotic biscuits with black soybean sprouts flour and standard rations and egg white flour at true digestibility (TD), biological values (BV) and Net Protein Utilization (NPU).Keywords : Prebiotic biscuits, Evaluation of protein quality, In Vivo